Using of Hugot Lines in Teaching Figures of Speech in Filipino Subject - Aragon, Jhoana Marie Lopez (Future Science / FSH-PH Publications, 2023)
Hugot lines are in casual used in different places, even in the classroom. It is a figure of speech. It is also an expression of deep emotion that was tried dig out and indirectly states but has relation to the past and feelings of the speaker. The aim of this study is determine the effects of Hugot line in teaching Figure of Speech or Tayutay in Filipino. The study had utilized Quasi-Experimental research design where assessment tests and narrative inquiry questionnaire was used to gather the required data. Convinience sampling was employed. Two classes have participated consisting of 100 participants or 50 students in each classes. The assessment instrument is composed of 20 questions pertaining to Figures of Speech. The narrative inquiry questionnaire consist of 1 question “What are the effects of Hugot Line in Teaching Figures of Speech?” Based from the results, it concludes that : there is no gap in pre-assessment of the two groups but larger gap in the post-assessment scores where experimental group is much higher; there is no significant differences in the scores in pre-assessment and post-assessments of the groups to each other. Also, 8 themes have emerged from their narratives, including; (a) Interesting, (b) Active Sharing, (c) Easier to Comprehend, (d) Fun, (e) Active in Classes, (f) Meaningful Discussions, (g) Easier to Remember, and (h) can relate to self. Based from the narratives of the students, it shows that there is a positive effect in the teaching process based from the narratives of the students.